PENGARUH HARGA, STORE ATMOSPHERE DAN PROMOSI INSTAGRAM TERHADAP MINAT BELI PRODUK PADA COFFEE SHOP SUNNY STORY WONOGIRI - Agustina, Krisna; Handaruwati, Indah (LPPM UNISDA, 2025)
This study has the purpose of analyzing the influence of price, store atmosphere, and Instagram promotion on buying interest at Sunny Story Coffee shop in Wonogiri. The population that became part of this study was all consumers of the sunny story wonogiri coffee shop. By utilizing the purposive sampling method, the criteria used include customers who have seen Sunny Story Wonogiri's Instagram Coffee Shop Instagram promotion, know the location of Sunny Story Coffee shop, and consumers who have received Sunny Story Coffee shop recommendations from friends or other people. A sample of 40 respondents was taken. The findings of the research that have been carried out indicate that partially, price variables and Instagram promotions have no effect on buying interest while store atmosphere has an influence on buying interest. Meanwhile, simultaneously the three variables mentioned affect buying interest. This aspect indicates that a marketing strategy that considers and develops a store atmosphere will provide great benefits for Sunny Story's business growth.